2022
DOI: 10.1038/s41598-022-09743-3
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of preterm premature rupture of membranes and its association with inter-pregnancy interval: a prospective cohort study

Abstract: Preterm premature rupture of membranes is one of the causes of premature birth and perinatal deaths, particularly in developing countries due to poor access and availability of medical resources to manage and sustain the pregnancy to term. Although, several risk factors for preterm premature rupture of membranes were identified, its association with inter-pregnancy interval was understudied. Therefore, we aimed to assess the incidence of preterm premature rupture of membranes and its association with inter-pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…All occur during pregnancy (5.8%). 17,18 In contrast, our study describes fetal outcomes in terms of fetal distress meconium staining CSF 18 (12%), Apgar score (p = 0.053) and NICU admission (p = 0.564). Patients presenting with pregnancy more than 24 weeks with a history or active per vaginal leak should be admitted, detailed obstetrics and per vaginal speculum examination to be performed should be observed for signs of chorioamnionitis and promptly treated with antibiotics cover and steroids coverage to prevent maternal endometritis and fetal respiratory distress syndrome.…”
Section: Discussionmentioning
confidence: 81%
“…All occur during pregnancy (5.8%). 17,18 In contrast, our study describes fetal outcomes in terms of fetal distress meconium staining CSF 18 (12%), Apgar score (p = 0.053) and NICU admission (p = 0.564). Patients presenting with pregnancy more than 24 weeks with a history or active per vaginal leak should be admitted, detailed obstetrics and per vaginal speculum examination to be performed should be observed for signs of chorioamnionitis and promptly treated with antibiotics cover and steroids coverage to prevent maternal endometritis and fetal respiratory distress syndrome.…”
Section: Discussionmentioning
confidence: 81%
“…The association between short IPI and placental abruption has been reported previously [ 28 ]. A possible explanation of this association could also be related to the previously mentioned theory of abnormal remodeling of the blood vessels in the endometrium among patients with short IPI [ 21 ].…”
Section: Discussionmentioning
confidence: 93%
“…For example, in a study that found a correlation between recurrent short IPI and PTB [ 20 ], it was argued that the findings of the study strengthened the “nutrient depletion theory,” and in a different study that found an association between short IPI and preterm premature rupture of membranes the conclusion was that the findings strengthened either the “cervical insufficiency theory” or a theory regarding the abnormal remodeling of the blood vessels in the endometrium [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Globally, the incidence of PROM is 1-4% of every pregnancy. A pregnancy interval less than 18 months is a risk factor for PROM (Jena et al, 2022).…”
Section: Discussionmentioning
confidence: 99%